EMOTIONS OF YOUNG ADULTS ON CRIME REPORTS AGAINST WOMEN - R.A. Rasi , KM Ashifa, Tariq Elhadary, Ms. Jeslin Anto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to understand young adults' emotions in perceiving crime reports about women. The study was conducted among young adults. Youngsters can possess different feelings and attitudes towards the crime news regarding women and negatively affect their day-to-day life. The general objective is to study the specific emotions of young adults while perceiving crime reports against women. Descriptive research design has been followed, and the method of study is quantitative. The study was conducted among regular engineering graduate students in Kerala. The study described the government's lack of accountability and young adults' anger towards the whole system. The study results say a significant relationship between perceiving crime reports and nervousness in young adults. This study can be directed in the future towards the emotions of parents while perceiving crime reports against women.